Tactile-kinesthetic stimulation to gain weight and reduce the length of stay care for premature baby at public hospitals of Semarang, Indonesia - Freya Nazera Iskandar; Ari Suwondo; Bedjo Santoso (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Premature babies are susceptible to a variety of health problems in early of their lives, thus, management of premature care should be designed to optimize the growth and development, with no more cost extension. The management of premature care by non-pharmacological treatments becomes popular nowadays, and applied in the hospital unit care, including the Tactile-Kinesthetic Stimulation (TKS) and Kangaroo Mother Care (KMC).Aims: This study is to present the effect of Tactile-Kinesthetic Stimulation (TKS) on weight gain and reduction length of stay care for premature babies, and to compare the results with the standard Kangaroo Mother Care (KMC) given at the hospital care unit.Methods: The study used a quasi-experimental design with pretest-posttest with a control group. A total of 32 premature babies was equally divided to a control group given a standard KMC procedure and an intervention group receiving the TKS. Sampling was done using a consecutive sampling method where the low birth weight infants were selected from two public hospitals in Semarang of Indonesia, with consent from the parents. Data was then analyzed by a repeated measure ANOVA, general linear model and Mann-Whitney test to find the significant mean difference at p value less than 0.05.Results: The data shows that the babies' weight significantly increased day by day only if the premature neonates received Tactile Kinesthetic Stimulation, gained 148.75 gram only 3 days after the initial measurement. However, from this study we noted that the premature babies' weight at the control group provided only with Kangaroo Mother Care slightly decreased at 35.69 gram at the third day of observation. In average, premature babies receiving TKS need only 3 days before return home, while if receiving the standard KMC the preterm babies required 5 days in the hospital care.Conclusion: Not only effective to gain the weight, giving Tactile-Kinesthetic Stimulation to the low birth weight baby shorter the length of stay in the hospital unit care. It suggests that the TKS intervention will provide good result in maintaining the weight of the low birth weight baby and will reduce the costs of staying in the hospital unit care. Keywords: Tactile-Kinesthetic Stimulation, Kangaroo Mother Care, Low birth weight, Length of stay care, Premature baby Received: 06 September 2018, Reviewed: 13 September 2018, Received: in revised form 24 October 2019, Accepted: 26 February 2019 DOI: 10.35898/ghmj-31553